2020
DOI: 10.1002/alr.22663
|View full text |Cite
|
Sign up to set email alerts
|

Central compartment atopic disease: the missing link in the allergy and chronic rhinosinusitis with nasal polyps saga

Abstract: Central compartment atopic disease the missing link in the allergy and chronic rhinosinusitis with nasal polyps saga There has been a long-standing debate on the relationship between allergy and chronic rhinosinusitis (CRS). Multiple studies have been published with mixed results for both CRS without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP). In an evidence-based review of the relationship between CRS and allergy, Wilson et al. 1 found no consistent association between allergy and CRSsNP and CRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…CCAD is a nasal inflammatory subtype of type 2 diffuse CRS characterized by polypoid degeneration of the central compartment of the nasal cavity, which includes either the postero-superior nasal septum, the middle turbinate, the superior turbinate, or in combination [ 60 , 83 ]. Overall, this central pattern of inflammatory changes is associated with 97.6% of prevalence of clinical AR [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…CCAD is a nasal inflammatory subtype of type 2 diffuse CRS characterized by polypoid degeneration of the central compartment of the nasal cavity, which includes either the postero-superior nasal septum, the middle turbinate, the superior turbinate, or in combination [ 60 , 83 ]. Overall, this central pattern of inflammatory changes is associated with 97.6% of prevalence of clinical AR [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of total opacifications of the bilateral maxillary sinuses excluded the subjects from the diagnosis of central compartment type CRS. With advanced stages of CRS, it is more difficult to radiologically distinguish central‐compartment‐type CRS from others 5 . Therefore, patients who had previously undergone sinus surgery and pansinusitis (the Lund‐Mackay scores >23) were also excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Central compartment atopic disease (CCAD), defined as the inflammation and edema of the central sinonasal compartment, is a phenotypic subtype of CRS first described in 2017, and it was reported to be associated with inhalant allergen sensitization 1–5 . The diagnosis of CCAD can be made endoscopically and/or radiographically 2,4,6 .…”
mentioning
confidence: 99%
“…Previous reports have showed that the MT and NS were the most frequent sites where allergens deposited. 3 , 4 The prevalence of allergy was higher (97.6%) while the prevalence of asthma was lower (17.1%) in CCAD patients than other CRSwNP subtypes. 5 …”
Section: Introductionmentioning
confidence: 90%
“… 2 CCAD is also defined as an inflammatory process that results from inhalant allergy, which provides a definitive link between allergy and CRSwNP. 3 The involvement of the central compartment area may be due to the deposition of allergen. Previous reports have showed that the MT and NS were the most frequent sites where allergens deposited.…”
Section: Introductionmentioning
confidence: 99%